2015
DOI: 10.1007/s11250-015-0957-6
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient requirements and low-cost balanced diets, based on seasonally available local feedstuffs, for local pigs on smallholder farms in Western Kenya

Abstract: Growth performance of pigs on smallholder farms in the tropics is low. Lack of feedstuffs, seasonal feed shortages, and feeding nutritionally unbalanced diets contribute to slow growth. Low-cost balanced diets are needed to improve pig performance. In this study, we estimated the nutrient requirements of local pigs on smallholder farms in Kenya and developed balanced low-cost diets using seasonally available local feedstuffs. Diets were formulated to provide pigs with 80 % of the nutrient density in corn and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Palm kernel meal is used in Southeast Asia, especially in pullet and laying hen diets [28]. Dried sweet potatoes, banana meal, and several other raw materials can be used in some countries but are not listed here because their use is highly specific and very localized [78,79]. …”
Section: Pig and Poultry Dietsmentioning
confidence: 99%
“…Palm kernel meal is used in Southeast Asia, especially in pullet and laying hen diets [28]. Dried sweet potatoes, banana meal, and several other raw materials can be used in some countries but are not listed here because their use is highly specific and very localized [78,79]. …”
Section: Pig and Poultry Dietsmentioning
confidence: 99%
“…This clearly highlights the need to redefine protein requirements for slow-growing indigenous pigs. Carter et al (2016) reported that the nutrient requirements of local pigs are lower than those of exotic breeds. An increase in ADFI and ADG as the week proceeded could be associated with an increase in body size from about 24.4 kg in week 1 to 39.8 kg in week 8.…”
Section: Discussionmentioning
confidence: 99%
“…with sand) is recommended. These are discussed in more detail in a subsequent manuscript where pig nutrient requirements, ingredient constraints, actual ration composition and estimated pig performance are reported (Carter et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%